Risk of invasive penile cancer after treatment of penile intraepithelial neoplasia - Bjartmar, Inessa; Gerdtsson, Axel; Torbrand, Christian; Kristiansen, Sinja (BJU International, 2025)
Objectives: To examine the risk of progression and time to progression from penile intraepithelial neoplasia (PeIN) to invasive penile cancer in patients treated for PeIN with either surgery, laser ablation or topical treatment, and to examine recurrence risk after treatment of PeIN. Patients and Methods: Data on patients diagnosed with PeIN (n = 1122) between 2000 and 2020 were extracted from the Swedish National Penile Cancer Registry (NPECR). Progression was defined as a second registration of invasive penile cancer in this registry. Additionally, patient charts from the three largest cities in Sweden (Stockholm, Gothenburg and Malmö) were analysed with regard to both progression of PeIN to invasive cancer and recurrence risk after treatment. Results: The NPECR included 1122 patients with PeIN, of whom 23 were re-registered as having invasive penile cancer. In the 927 PeIN patients for whom data on treatment were available, re-registration of invasive cancer was seen in 13 patients after surgery, six after laser ablation, and one after topical treatment. The progression-free probabilities at 24 months in these treatment groups were 99.3% (95% confidence interval [CI] 0.987; 0.999), 100% (95% CI 1.000; 1.000) and 98.8% (95% CI 0.965; 1.000), respectively (log-rank test P = 0.192). In the Stockholm, Gothenburg and Malmö cohort, 253 patients with PeIN were followed and 14 developed invasive penile cancer. Of the 247 PeIN cases with data on treatment, four progressed after surgery, eight after laser ablation, and one after topical treatment. The progression-free probabilities at 24 months in these treatment groups were 98.2% (95% CI 0.956; 1.000), 86.2% (95% CI 0.744; 0.997) and 100% (95% CI 1.000; 1.000), respectively (log-rank test P < 0.001). Conclusion: We found that PeIN has a low risk of progressing into invasive penile cancer regardless of treatment modality. However, laser ablation therapy is not recommended due to a higher risk of progression after such treatment compared to surgical and topical treatment. We recommend individualised follow-up protocols of PeIN based on treatment and lesion location.
Keywords: human papillomavirus; lichen sclerosus; penile cancer; penile intraepithelial neoplasia; squamous cell carcinoma in situ